Identifying Al-Ashil and Al-Dakhil Elements in Al-Khazin's Exegesis of QS. Yusuf: 23-24 - Nova, Murti Aria Diah; Nisa, Fauziatun; Rohman, Abdur (QiST: Journal of Quran and Tafseer Studies, 2026)
The study of classical exegesis is important in order to maintain the authenticity of Qur'anic interpretation. The research gap of this study lies in the limited number of works that classify the elements of al-ashīl and al-dakhīl at the level of specific verses in Tafsir al-Khazin. Although widely known and frequently used, this commentary is often considered to contain elements of al-dakhīl, especially through isrā'īliyyāt narratives. This raises the question, how the elements of al-ashīl and al-dakhīl can be identified in the interpretation of QS. Yusuf, verses 23-24, in Tafsir al-Khazin? This study aims to analyze and classify these elements and assess their implications for understanding the story of Prophet Yusuf. The selected verses are significant because they contain a well-known narrative that has attracted broad attention. The research employs a qualitative, library-based approach, using descriptive-critical analysis of the exegetical text, the cited narrations, and comparisons with the principles of interpretation and prophetic infallibility. The findings of this study indicate that the al-ashīl elements in al-Khazin's tafsir are identified through the use of Qur'anic verses, hadith, and authentic scholarly opinions. Meanwhile, the al-dakhīl elements are identified through fabricated isrā'īliyyāt reports that contradict the principle of prophetic infallibility and are presented without adequate critical examination. In fact, the use of al-dakhīl elements appears to be more dominant than al-ashīl elements. This study has the potential to offer a methodological contribution to Qur'anic exegesis and to support efforts to preserve the authenticity of interpretation within the broader scholarly discourse.